Respuesta :

Answer:

[tex]f^{-1}(x) = \sqrt[5]{\frac{x+7}{9} -10}[/tex]

Explanation:

given : f(x) = 9( [tex]x^5[/tex] + 10 ) - 7

replace x and y with each other.

  • x = 9( [tex]y^5[/tex] + 10 ) - 7

solve for y

  • x + 7 = 9( [tex]y^5[/tex] + 10 )
  • ( [tex]y^5[/tex] + 10 ) = [tex]\frac{x + 7}{9}[/tex]
  • [tex]y^5[/tex] + 10 = [tex]\frac{x + 7}{9}[/tex]
  • [tex]y^5[/tex] = [tex]\frac{x + 7}{9}[/tex] - 10
  • y = [tex]\sqrt[5]{\frac{x+7}{9} -10}[/tex]

Therefore,

  • [tex]f^{-1}(x) = \sqrt[5]{\frac{x+7}{9} -10}[/tex]